Metastases-directed stereotactic body radiotherapy in combination with targeted therapy or immunotherapy: systematic review and consensus recommendations by the EORTC–ESTRO OligoCare consortium. Issue 3 (March 2023) - Kroeze, Stephanie G C; Pavic, Matea; Stellamans, Karin; Lievens, Yolande; Becherini, Carlotta; Scorsetti, Marta; Alongi, Filippo; Ricardi, Umberto; Jereczek-Fossa, Barbara Alicja; Westhoff, Paulien; But-Hadzic, Jasna; Widder, Joachim; et al.
Summary: Stereotactic body radiotherapy (SBRT) for patients with metastatic cancer, especially when characterised by a low tumour burden (ie, oligometastatic disease), receiving targeted therapy or immunotherapy has become a frequently practised and guideline-supported treatment strategy. Despite the increasing use in routine clinical practice, there is little information on the safety of combining SBRT with modern targeted therapy or immunotherapy and a paucity of high-level evidence to guide clinical management. A systematic literature review was performed to identify the toxicity profiles of combined metastases-directed SBRT and targeted therapy or immunotherapy. These results served as the basis for an international Delphi consensus process among 28 interdisciplinary experts who are members of the European Society for Radiotherapy and Oncology (ESTRO) and European Organisation for Research and Treatment of Cancer (EORTC) OligoCare consortium. Consensus was sought about risk mitigation strategies of metastases-directed SBRT combined with targeted therapy or immunotherapy; a potential need for and length of interruption to targeted therapy or immunotherapy around SBRT delivery; and potential adaptations of radiation dose and fractionation. Results of this systematic review and consensus process compile the best available evidence for safe combination of metastases-directed SBRT and targeted therapy or immunotherapy for patients with metastatic or oligometastatic cancer and aim to guide today's clinical practice and the design of future clinical trials.